Flow Chemistry of Metal Carbenoid Species towards Selective Organic Synthesis - Okamoto, Kazuhiro; Nagaki, Aiichiro (Synthesis, 2024)
This review deals with C1 carbenoid chemistry, with a focus on lithium carbenoid species generated in flash flow systems. Strict control of the temperature, residence time, and mixing efficiency has led to various transformation reactions involving epoxidation, cyclopropanation, and homologation, among others. The use of other metal species, including trifluoromethylpotassium (CF3K) and magnesium/ zinc carbenoids, in flow systems is also introduced.1 Introduction1.1 Lithium Carbenoids in C1 Chemistry1.2 Flow Chemistry for C1 Lithium Carbenoids2 Flow Reactions Involving Carbenoid Species2.1 Deprotonative Generation of Lithium Carbenoid Species2.2 Generation of Lithium Carbenoid Species via Halogen–Lithium Exchange2.3 Generation of Lithium Carbenoid Species via Reductive Lithiation2.4 Generation of Lithium Carbenoid Species via Alkyllithiation2.5 Generation of Trifluoromethylpotassium Species in Flow2.6 Generation of Other Metal Carbenoid Species3 Conclusion
Keywords: flow chemistry; carbenoids; C1 chemistry; flash chemistry; organometallic reagents